Analyzing Threat Level of the Backdoor Attack Method for an Organization’s Operation - Mohd Nasharuddin, Muhammad Zafran Syahmi; Abubakar, Adamu (International Journal on Perceptive and Cognitive Computing, 2024)
Backdoor attacks played a critical part in the catastrophe, as well as the overall impact of cyberattacks. Backdoor assaults are additionally influencing the landscape of malware and threats, forcing companies to concentrate more on detecting and establishing vulnerability tactics in order to avoid hostile backdoor threats. Despite advances in cybersecurity systems, backdoor assaults remain a source of concern because of their propensity to remain undetected long after the attack vector has been started. This research is aimed to examine the threats of backdoor attack methods in an organization's operational network, provide a full-scale review, and serve as direction for training and defensive measures. The fundamental inspiration was drawn from the alarming and involving threat in cybersecurity, which necessitates a better awareness of the level of risk and the concurrent requirement for increased security measures. Most traditional security solutions usually fail to detect harmful backdoors due to the stealthy nature of backdoor code within the system, necessitating a unique approach to full-scale threat analysis. A multi-phase approach that begins with considerable reading and examination of existing literature to get insight into typical backdoor attack methodologies and application methods. Following analysis, testing was carried out in a virtual lab in a controlled environment because thorough malware analysis testing must adhere to ethical and legal cyber testing laws to avoid any penalties or foolish breaches. This methodology also included testing on numerous attack channels combined with backdoor attacks, such as detecting software vulnerabilities, phishing emails, and direct payload injection, to determine the complexity of the different attack vectors. Each of the collected data is utilized to create a threat model that predicts the amount of risk associated with the backdoor attack approach. The finding contributes to the development of more resilient defence mechanisms, while also strengthening the overall organization's security architecture and protocols.